A cluster randomized trial of provider incentives for anaemia reduction in rural China - Miller, Grant; Renfu Lou; Linxiu Zhang; Sylvia, Sean; Yaojiang Shi; Foo, Patricia; Qiran Zhao; Martorell, Reynaldo; Medina, Alexis; Rozelle, Scott (2012)
This study tested the impact of performance pay for anemia reduction in rural China to determine how misaligned supply-side incentives impede health programs in developing countries. This study is probably the first to evaluate performance pay for actual health improvement. It conducted a cluster randomized trial for information, subsidies, and incentive for school principals to reduce anemia among fourth and fifth grade students in 72 randomly-selected rural primary schools across northwest China.
Keywords: Anemia; China